The role of foreign and domestic firms in regional innovation systems of latecomer countries: empirical evidence from the electronics industry in the Pearl River Delta - Schiller, Daniel (ERDKUNDE, 2011)
The literature on technological change and regional development in latecomer countries has argued that foreign and domestic firms differ markedly with regard to their innovation and upgrading efforts. Foreign firms tend to possess greater initial technological capabilities and better access to advanced technologies, but often retain advanced production and innovation activities at their home bases. Some domestic firms, on the other hand, enter the market with fewer resources and lower technological capabilities, but make great efforts to learn. It thus remains a matter of debate as to whether foreign or domestic firms are contributing to the formation and upgrading of regional innovation systems in late-comer countries. This paper provides empirical evidence for the innovation activities of foreign and domestic Chinese firms by testing theoretically-based hypotheses with company survey data from 222 electronics firms in the Pearl River Delta in South China. The major findings are that non-domestic firms carry out innovation activities with greater intensity and more external collaboration than domestic firms. The potential for the emergence of a more coherent regional innovation system and a technological catch-up to the standard of the non-domestic incumbents on the part of domestic electronics firms is rather limited.